STRATEGI GURU DALAM MENANAMKAN NILAI MULTIKULTURAL MELALUI PEMBELAJARAN IPS DI SEKOLAH - Salsabila Fitria Salsa; Ahmad Fauzan Nafis; Mia Sri Dwi Yanti; Nashuha; Nurmarito Rambe (STKIP Subang, 2026)
This study aims to describe the strategies of social studies teachers in instilling multicultural values in MAN 2 Model Medan, the values instilled, as well as their supporting and inhibiting factors. Using a descriptive qualitative approach, data was collected through observation, interviews with social studies teachers, and documentation. The results showed that teachers used contextual learning strategies, heterogeneous group discussions, and case studies to build tolerance attitudes. The values instilled include tolerance, cooperation, and unity. Despite the obstacles in the form of minor bullying behavior, teachers interpersonal approaches have proven to be effective in improving students social attitudes at school.